Risk Factors of Leptospirosis in Klaten, Central Java - Maya Sofiyani; Ruben Dharmawan; Bhisma Murti (Journal of Epidemiology and Public Health, 2018)
Background: Leptospirosis a global public health issue, particullary in tropical and sub-tropical countries with high precipitation. WHO has estimated that the annual of Leptospirosis is 0.1 to 1 case/100,000 population in moderate non-endemic area, and 10 to 100 cases/100,000 population in humid and tropical endemic areas. Currently, Indonesia is a tropical country with the highest fatality rate of leptospirosis, ranging from 2.5% to 16.45% with an average of 7.1%. It places Indonesia as the third country with the highest mortality attibutable to Leptospirosis. This study aimed to analyze the risk factors of Leptospirosis in Klaten, Central Java.Subjects and Method: This was an analytic and observational study with case control design. The study was conducted in Klaten, Central Java, from October to November, 2017. A sample of 49 Leptospirosis cases and 101 non-diseased controls were selected for this study by fixed disease sampling. The independent variable were employment status, history of cuts, history of water excursion, use of personal protective equipment (PPE), house condition, environmental condition, presence of mouse or cattle, history of rain or flood. The dependent variable was Leptospirosis. The data were collected by questionnaire and analyzed by path analysis.Results: The risk of Leptospirosis increased with history of cuts (b= 1.64; CI 95%= 0.40 to 2.87; p= 0.009), history of water excursion (b= 1.98; CI 95%= 0.52 to 3.43; p= 0.008), poor house condition (b= -1.92; CI 95%= -3.08 to -0.77; p= 0.001), and poor environmental condition (b= -2.35; CI 95%= -3.48 to -1.23; p<0.001). History of cuts increased with cattle-related work (b= 1.79; CI 95%= 0.86 to 2.72; p<0.001) and absence of PPE (b= -2.54; CI 95%= -3.49 to -1.60; p<0.001).Conclusion: The risk of Leptospirosis increases with history of cuts, history of water excursion, poor house condition, and poor environmental condition. History of cuts increases with cattle-related work and absence of PPE.Keywords: risk factor, LeptospirosisCorrespondence: Maya Sofiyani. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta, 57126, Central Java, Indonesia. Email: mayasofiani@rocketmail.com.Journal of Epidemiology and Public Health (2018), 3(1):  11-24https://doi.org/10.26911/jepublichealth.2018.03.01.02